2003
DOI: 10.1007/bf03166685
|View full text |Cite
|
Sign up to set email alerts
|

Spin-lattice and spin-spin relaxation times of 2,4,6-tri-tert-butyl phenoxyl and 2,6-di-tert-butyl-4-methyl phenoxyl in diamagnetic crystals: Relaxation mechanism and influence of molecular motions

Abstract: The spin-lattice and phase-memory times were determined for 2,4,6-tri-tert-butyl phenoxyl and 2,6-di-tert-butyl-4-methyl phenoxyl dispersed in a diamagnetic matrix by use of p¡ and stimulated echoes. The temperature variations from room temperature and lower to liquid helium indicated interesting characte¡ albeit there were no echo signals between 150 and 100 K. It may be concluded that the relaxation times vary depending on the motional fluctuation of substituted molecular groups on the n-conjugated framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It was confirmed that both methods could produce the corresponding phenoxyl radicals diluted in the diamagnetic crystals, i.e., the primary phenol, 11,15 giving the same ESR spectra. (I′) can be obtained only by UV irradiation, since, in solution, the generated (I′) can instantly dimerize (as shown in Scheme 2), becoming diamagnetic and ESR-silent.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…It was confirmed that both methods could produce the corresponding phenoxyl radicals diluted in the diamagnetic crystals, i.e., the primary phenol, 11,15 giving the same ESR spectra. (I′) can be obtained only by UV irradiation, since, in solution, the generated (I′) can instantly dimerize (as shown in Scheme 2), becoming diamagnetic and ESR-silent.…”
Section: Methodsmentioning
confidence: 77%
“…Precursor phenols purchased commercially (I−V) or synthesized following the procedure described in the literature (VI 11 ) were recrystallized from a toluene solution at room-temperature several times and UV-irradiated in vacuo for 4 or 5 h for the radical generation with a high-pressure mercury lamp manufactured by Ushio Electric Inc (shown in Scheme ) . It was found that these generated radicals are dispersed homogeneously in the diamagnetic matrixes of the corresponding phenols, , just like the system of γ-irradiation .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the silica nanostructure, the relaxation times are longer than those measured in solution for the same radicals; they are even longer than those of the nitroxides typically used in DNP NMR as polarizing agent . In addition, two other points drew our attention: (i) SBA n -SO exhibits relaxation times that are on the order of those of SBA n -OO and (ii) the two sulfur- and oxygen-centered radicals have different g -values (see CW, X-, Q-, and W-band results).…”
Section: Electron Spin Relaxation Properties Of the Radicalsmentioning
confidence: 95%